2003
DOI: 10.1093/jac/dkg290
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and activity of cethromycin (ABT-773) within human polymorphonuclear leucocytes

Abstract: Cethromycin achieves high intracellular concentrations within human PMNs, remaining active intracellularly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…for ␤-lactams of between Ϫ0.68 log CFU (oxacillin) and Ϫ0.90 log CFU (imipenem). These earlier studies of conventional antibiotics also found a much lower intracellular activity than would have been expected from extracellular killing kinetics and from the levels of intracellular accumulation, indicating a low correlation between the intracellular activity and the level of accumulation (4,12,29,30,36). Furthermore, the phenomenon of decreased relative efficacies could be caused by several factors such as acidic pH conditions, binding to intracellular proteins or other constituents, or changes in the metabolism of the bacteria (4,36).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…for ␤-lactams of between Ϫ0.68 log CFU (oxacillin) and Ϫ0.90 log CFU (imipenem). These earlier studies of conventional antibiotics also found a much lower intracellular activity than would have been expected from extracellular killing kinetics and from the levels of intracellular accumulation, indicating a low correlation between the intracellular activity and the level of accumulation (4,12,29,30,36). Furthermore, the phenomenon of decreased relative efficacies could be caused by several factors such as acidic pH conditions, binding to intracellular proteins or other constituents, or changes in the metabolism of the bacteria (4,36).…”
Section: Discussionmentioning
confidence: 90%
“…While in vitro models using either human or animal cell lines have been developed to study the intracellular activity of antibiotics (4,12,13,15,38), we lack effective animal models. Sandberg et al recently described a model where both the extra-and intracellular antimicrobial effects on S. aureus were studied in a modified version of the mouse peritonitis model (32).…”
mentioning
confidence: 99%
“…Actually, the strain studied here has been widely used for the evaluation of the in vitro activities of new antibiotics in broth (61) as well as in phagocytes (24). The choice of a unique, well-characterized strain was actually essential for addressing the question of antibiotic intracellular activity per se and avoiding the blurring of the results because of other factors that can modulate the intracellular response to antibiotics, such as virulence and variations in the expression of resistance mechanisms.…”
mentioning
confidence: 99%
“…We did not directly measure intracellular antimicrobial activity in AC, and the presence of the drug does not confirm antimicrobial activity. However, intracellular cethromycin has been reported to accumulate and to retain its antimicrobial activity within polymorphonuclear cells (13). A larger dose would also yield C max ELF concentrations that would likely exceed the MIC 90 for H. influenzae; however, the determination of the duration above MIC 90 and other pharmacodynamic parameters requires further investigation.…”
Section: Discussionmentioning
confidence: 99%